Detection of hemoparasites in dairy cattle from the state of Espírito Santo - Gonçalo Nunes Silva Neto; Alexandre Scherre Tomazinho Bonisson; Camila Angela Marques; Tiago Facury Moreira; Emy Hiura; Fabio Ribeiro Braga; Odael Spadeto Junior; Rosangela Zacarias Machado; Otavio Luiz Fidelis Junior (Pubvet, 2021)
The objective of this study was to verify the occurrence of Anaplasma marginale, Babesia bovis and Babesia bigemina in dairy cattle from the central mesoregion of the State of Espírito Santo, through direct parasitological tests (blood smears) and serological tests (Enzyme Linked Immunosorbent Assay - ELISA). Blood samples were collected from 159 animals from 6 farms, concentrated in the central mesoregion of the state of Espírito Santo. The blood collected was stored in EDTA tubes, used to perform blood smears, and in tubes without anticoagulant, to obtain serum. The sera obtained were used for the detection of IgG antibodies to A. marginale, B. bovis and B. bigemina. Of the 159 blood smears analyzed, 64 (40.2%) and 11 (6.9%) were positive for A. marginale and Babesia sp., respectively. The ELISA of the 159 samples, 9 (5.7%), 59 (37.1%) and 47 (29.5%) were seropositive for A. marginale, B. bovis and B. bigemina, respectively. The results obtained characterize these farms of the central mesoregion of the state of Espírito Santo, as of enzootic instability for Bovine Parasitic Sadness (TPB) agents, presenting a high risk of occurrence of anaplasmosis and babesiosis outbreaks.